2017
DOI: 10.3390/en10101613
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Electricity-Load Forecasting Using a TSK-Based Extreme Learning Machine with Knowledge Representation

Abstract: This paper discusses short-term electricity-load forecasting using an extreme learning machine (ELM) with automatic knowledge representation from a given input-output data set. For this purpose, we use a Takagi-Sugeno-Kang (TSK)-based ELM to develop a systematic approach to generating if-then rules, while the conventional ELM operates without knowledge information. The TSK-ELM design includes a two-phase development. First, we generate an initial random-partition matrix and estimate cluster centers for random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…(2) The temperature. As people use temperature-adjusting devices to adapt to the temperature, in a previous study [23][24][25], temperature was considered as an essential input feature and the forecasting results were accurate enough. In this paper, the maximum temperature, the minimum temperature and the average temperature are selected as factors.…”
Section: Selection Of Influenced Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The temperature. As people use temperature-adjusting devices to adapt to the temperature, in a previous study [23][24][25], temperature was considered as an essential input feature and the forecasting results were accurate enough. In this paper, the maximum temperature, the minimum temperature and the average temperature are selected as factors.…”
Section: Selection Of Influenced Indexesmentioning
confidence: 99%
“…In addition, there are still many other external weather factors that may also potentially influence the power load. Only Energies 2018, 11, 1282 3 of 18 considering the temperature as the input variable may be not enough [23][24][25], and other meteorological factors such as humidity, visibility and air pressure etc. also should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, they have become more and more popular in energy forecasting. Typical AI models include support-vector regression (SVR) and its extension least-squares SVR (LSSVR) [5,6], artificial neural network (ANN) [7][8][9], extreme learning machine (ELM) [10], sparse Bayesian learning (SBL) [11,12], deep learning [13] (stacked denoising autoencoders (SDAs) [14], deep belief network (DBN) [15], convolutional neural network (CNN) [16], and long short-term memory (LSTM)) [17]), and nature-inspired optimization algorithms [18,19]. For example, Chen et al put forward a new SVR model that used the temperature before demand response as additional input variables for STLF [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kulkarni et al proposed a spiking neural network to forecast short-term load with consideration of weather variables [8]. Yoem and Kwak used an ELM with knowledge representation for STLF, and the experimental results indicated good performance of the approach [10]. Han et al presented time-dependency CNN and cycle-based LSTM for STLF by mapping the load data as pixels and rearranging them into a 2-D image, and the extensive experiments demonstrated that the proposed models were superior to the compared models in terms of computation complexity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to [24], the connection weight γ between the hidden layer and the output layer can be obtained by solving the least square solution of the equations listed as follows:…”
Section: Basic Principles Of Extreme Learning Machine (Elm)mentioning
confidence: 99%